2013
DOI: 10.3402/ijch.v72i0.21167
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of caregiver reported Severe Early Childhood Caries in Manitoba First Nations children: results from the RHS Phase 2 (2008–2010)

Abstract: ObjectivesThe high prevalence and severity of caries among Canadian First Nations children is a growing concern. Dental surgery in hospital is often necessary to treat the signs of decay but does not address the underlying factors contributing to its development. The purpose of this study was to determine the prevalence and risk factors of caregiver-reported Baby Bottle Tooth Decay (BBTD), or Severe Early Childhood Caries (S-ECC), among preschool children recruited in Phase 2 of the First Nations Regional Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 25 publications
4
65
3
4
Order By: Relevance
“…The results of this study were in accordance with several previous studies [Schroth et al, 2013a;Li et al, 2017;Peres et al, 2017]. In Japan, "no residence tax" means low household income.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study were in accordance with several previous studies [Schroth et al, 2013a;Li et al, 2017;Peres et al, 2017]. In Japan, "no residence tax" means low household income.…”
Section: Discussionsupporting
confidence: 82%
“…Some previous studies in developing countries reported that risk factors associated with S-ECC were frequent or prolonged breastfeeding [Özen et al, 2016;Feldens et al, 2018], socioeconomic status [Schroth et al, 2013a;Li et al, 2017;Peres et al, 2017], not having help with brushing [Turton et al, 2016;Mangla et al, 2017], and snacking habits [Evans et al, 2013;Mangla et al, 2017;Peres et al, 2017;Sun et al, 2017]. However, it is unclear whether these risk factors for S-ECC are similarly associated with S-ECC in developed countries.…”
Section: Introductionmentioning
confidence: 98%
“…Supervised tooth brushing with fluoride toothpaste has been associated with a 20–30% reduction in caries prevalence in other countries [34]. Lack of familiarity with children’s dental health condition, low general oral health knowledge, and negative dental disease preventive behaviors were revealed in this population, which might be attributable to parental educational qualifications and to socioeconomic and cultural status, as previously observed [18, 23, 29, 37]. Parents also underestimate the importance of deciduous teeth, because they are replaced by permanent teeth.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies had found that the level of education of caregivers, especially mothers, was notably associated with undertaking preventive measures in children (44)(45)(46). In our study, the education of caregivers was relatively high: 63% of participants had university degree and the others were high school graduates.…”
Section: Acta Facultatis Medicaementioning
confidence: 62%